Early marriage is a risk factor for stunting in children in Gunungkidul Regency - Tengjaya, Angelia Anisa Amelia; Nai, Hildagardis Meliyani Erista; Purnawijayanti, Hiasinta Anatasia (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2025)
Background: The prevalence of stunting in 2022 in Indonesia is still high, namely 21.6%. Stunting in children under five can be caused by nutritional problems during the first 8000 days of life. The mother's age at marriage can also cause stunting in children under five. There are 312 incidents of early marriage (married at <19 years of age) in Gunungkidul Regency in the period 2017-2022.Objective: to analyze the relationship between early marriage and the incidence of stunting in children aged 0-59 months in Gunungkidul Regency.Method: The study used a retrospective cohort design with exposed and unexposed sample groups of 65 people each. The sampling technique uses simple random sampling. Data on the age of early marriage was obtained from records at the Gunungkidul Regency Religious Affairs Office. Data were collected on sample characteristics, breastfeeding status, and child infectious diseases using interview techniques using a questionnaire. The incidence of stunting is assessed by measuring body length or height.Results: Result of the bivariate analysis showed that there was a significant relationship between the mother's age at marriage (RR=25.4; CI=5.72-112.62; p=0.000), gender of the child (RR=2.37; CI=1 .02-5.4; p=0.040), history of acute respiratory infections (RR=4.80; CI=2.03-11.34; p=0.000), and history of diarrhea (RR=5.1; CI=2.16-12.08; p=0.000) with the incidence of stunting in children aged 0-59 months. Multivariate analysis showed that maternal age at marriage, (OR=36.5; CI=6.82-195.52; p=0.000), history of acute respiratory infections (OR=3.32; CI=1.09-1.09; p=0.035), and a history of diarrhea (OR=6.9; CI=2.19-22.15; p=0.001) influence the incidence of stunting.Conclusion: Early marriage, history of acute tract infections, and history of diarrhea are risk factors for stunting in children aged 0-59 months in Gunungkidul Regency.